2011
DOI: 10.1177/1362361310386505
|View full text |Cite
|
Sign up to set email alerts
|

The everyday routines of families of children with autism

Abstract: The purpose of this qualitative study was to explore the lived experience of how sensory-related behaviors of children with autism affected family routines. In-depth semi-structured interviews were conducted with four primary caregivers regarding the meaning and impact of their child's sensory-related behaviors on family routines that occurred inside and outside the home. Findings indicated that sensory behaviors are one factor that limited family participation in work, family and leisure activities; and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
143
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(151 citation statements)
references
References 19 publications
4
143
0
4
Order By: Relevance
“…On all measures, the ASD group had higher (more problematic) mean scores than the TD group on sensory and mealtime behavior measures. This finding is consistent with empirical findings reported in the literature (Jasmin et al, 2009;Keen, 2008;Nadon et al, 2011aNadon et al, , 2011bSchaaf et al, 2011). This study is unique because it also examined the relationships among sensory differences and mealtime behaviors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…On all measures, the ASD group had higher (more problematic) mean scores than the TD group on sensory and mealtime behavior measures. This finding is consistent with empirical findings reported in the literature (Jasmin et al, 2009;Keen, 2008;Nadon et al, 2011aNadon et al, , 2011bSchaaf et al, 2011). This study is unique because it also examined the relationships among sensory differences and mealtime behaviors.…”
Section: Discussionsupporting
confidence: 82%
“…American Journal of Occupational Therapy, 69, 6905185050. http://dx.doi.org/ 10.5014/ajot.2015.016790 S elf-care tasks, or activities of daily living (ADLs) such as grooming, eating, and dressing, are essential tasks for children to acquire as they mature. Increasing evidence has shown that children with autism spectrum disorder (ASD) experience challenges in these daily routines and that their sensory differences often interfere with their ability to develop skills in these important daily routines Schaaf, Toth-Cohen, Johnson, Outten, & Benevides, 2011;Stein, Polido, & Cermak, 2012;Stein, Polido, Mailloux, Coleman, & Cermak, 2011). Eating difficulties are a frequent problem for children with autism (Hubbard, Anderson, Curtin, Must, & Bandini, 2014;Kral, Eriksen, Souders, & Pinto-Martin, 2013;Marí-Bauset, Zazpe, Mari-Sanchis, Llopis-González, & Morales-Suárez-Varela, 2014;Nadon, Feldman, Dunn, & Gisel, 2011a, 2011bSchreck & Williams, 2006;Schreck, Williams, & Smith, 2004;Suarez, Nelson, & Curtis, 2014) and may weaken their physical health Lukens & Linscheid, 2008;Sharp et al, 2013), cause difficulty during family mealtimes and milieu (Bagby, Dickie, & Baranek, 2012;Schaaf et al, 2011;Suarez, Atchison, & Lagerwey, 2014), and impede participation in the educational setting (Koenig & Rudney, 2010).…”
mentioning
confidence: 99%
“…C hildren with autism spectrum disorder (ASD) often demonstrate unusual responses to sensory stimuli (i.e., sensory features; Baranek, Little, Parham, Ausderau, & Sabatos-DeVito, 2014;Ben-Sasson et al, 2009;Schaaf & Lane, 2015), which can present challenges for families in daily life (Bagby, Dickie, & Baranek, 2012;Lane, Young, Baker, & Angley, 2010;Schaaf, Toth-Cohen, Johnson, Outten, & Benevides, 2011). Sensory features in children with ASD have been classified into four sensory response patterns in a recent factor analytic study : hyperresponsiveness (i.e., an exaggerated response to sensory stimuli); hyporesponsiveness (i.e., a delayed or lack of response to sensory stimuli); enhanced perception (i.e., superior acuity of sensory stimuli); and sensory interests, repetitions, and seeking behaviors (i.e., fascination with or craving for intense sensory stimuli).…”
mentioning
confidence: 99%
“…In the current conceptualization, the term environment includes both the physical environment, such as the home and the classroom, and the cultural, social, temporal, and virtual environments (AOTA, 2014). For example, some sensory aspects of the physical environment can diminish a child's ability to learn and participate in important daily activities (Barrett, Zhang, Moffat, & Kobbacy, 2013;Reynolds et al, 2011;Schaaf, Toth-Cohen, Johnson, Outten, & Benevides, 2011). Classroom environments can be stimulating (Choi & McPherson, 2005;Crandell & Smaldino, 2000;Shield & Dockrell, 2003), and visual and auditory stimuli in particular may distract students from learning activities (Fisher, Godwin, & Seltman, 2014;Godwin & Fisher, 2011;Klatte, Bergström, & Lachmann, 2013).…”
Section: Environmental Supports and Adaptationsmentioning
confidence: 99%